2021
DOI: 10.4081/monaldi.2021.1668
|View full text |Cite
|
Sign up to set email alerts
|

Apparently normal epicardial coronaries in a patient with inferior wall myocardial infraction on the background of mild coronavirus disease-2019: take a second look!

Abstract: The coronary angiographic (CAG) findings of ST elevation myocardial infarction (STEMI) in patients of coronavirus disease 2019 (COVID-19) range from increased coronary artery thrombus burden to normal coronaries due to STEMI mimics. Here we report the case of a 45-year-old gentleman who presented with evolved inferior wall myocardial infarction with ongoing angina along with mild COVID-19. CAG showed normal epicardial coronaries except for distal right posterior descending coronary artery (RPDA) 100% occlusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The COVID-19 pandemic, along with respiratory failure, gave rise to cardiological complications. Studies have revealed that the prevalence of cardiovascular diseases was high during the COVID-19 surge [2], [3].Researches conducted during the ICU admissions also revealed the difficulty in recovery of patients with existing cardiovascular complications like coronary artery disease, heart failure and stroke, myocardial and atherosclerosis conditions mostly [4]. One of the study conducted in China…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic, along with respiratory failure, gave rise to cardiological complications. Studies have revealed that the prevalence of cardiovascular diseases was high during the COVID-19 surge [2], [3].Researches conducted during the ICU admissions also revealed the difficulty in recovery of patients with existing cardiovascular complications like coronary artery disease, heart failure and stroke, myocardial and atherosclerosis conditions mostly [4]. One of the study conducted in China…”
Section: Introductionmentioning
confidence: 99%